1255 A point-of-care test useful to detect underdiagnosed coelic disease in children. (17th August 2022) - Bondin, Ramon; Aquilina, Samuel; Grima, Anne-Marie; Vella, Cecil; Sorce, Salvatore; Giuliano, Angele; Brusca, Ignazio; Fregapane, Maria; Barbara, Christopher; Magazzu, Giuseppe; Raso, Giuseppe
Abstract : Aims: This study, part of a project on a Decision Support System (DSS) on coeliac disease (CD), aimed at assessing the usefulness of a minimally invasive, cheap Point-of-Care Test (POCT) in a population of school children, who underwent the largest CD screening program done to date. Methods: Ethics approval was granted to screen up to 20000 children between 3 and 13 years of age. An information leaflet was handed to the subjects through their respective schools. This also contained a questionnaire and consent form. The chosen POCT was able to detect anti-tissue transglutaminase antibodies IgM, IgA and IgG. Anonymized information was inserted into a computer database, by means of a user-friendly interface. The information retained included the answers of the questionnaire and POCT results. The children who were found to have a positive POCT, as well as the children who had at least 5 symptoms, were recalled and offered further testing. POCT was validated, according to 2012 ESPGHAN guidelines, against reference results of histology or against another anti-TG2 antibody test with performance similar to anti-endomysial antibodies. Diagnostic accuracy and post-test probability were calculated using the all-purpose 4-fold Table Analyzer and the interactive nomogram for post-test probability offered by the page of the Center for Evidence Based Medicine (http://cebmjr2.ox.ac.uk/). Results: By screening 19, 923 children, we found 137 POCT 'positive' cases. Out of 134 children who accepted and completed further investigations, 123 were positive at anti-TG2 antibody test and 11 negative. Final diagnosis of CD was made in 105 subjects. Eighty-three fulfilled the serological diagnostic criteria according to the new ESPGHAN guidelines 2020 and 56% of the diagnosed children had no symptoAmong 19584 children with POCT negative, 374 had 5 or more symptoms and 166 accepted further investigations: 2 resulted tTG positive and 4 borderline (< 2 times the upper limit of normal). In one case, CD was confirmed and investigations are pending in the other five. In the whole population, POCT sensitivity, specificity, positive and negative predictive values were 98% (96%CI, 95-100), 94% (95%CI, 90-97), 92% (95%CI, 87-96) and 99% (95%CI, 97-100), respectively. Likelihood ratio + was 15.3 (95%CI, 8.6-27.1). Considering a pre-test probability of CD 1% in the general paediatric population regardless of symptoms and 42% (95%CI, 37-48) such as that found in our population also with 5 or more symptoms, post-test probability was 13% and 92%, respectively. Conclusion: As CD is largely under diagnosed, POCT, with its high negative predictive value may be a valuable tool for mass screening. It may also be valuable at the pediatrician's office whereby in the presence of symptoms, a positive POCT result should prompt further testing.